Purification and characterization of DR_2577 (SlpA) a major S-layer protein from Deinococcus radiodurans - Farci, Domenica; Bowler, Matthew W.; Esposito, Francesca; McSweeney, Sean; Tramontano, Enzo; Piano, Dario (Frontiers in Microbiology, 2015)
The protein DR_2577 is a major Surface layer component of the radio-resistant bacterium Deinococcus radiodurans. In the present study DR_2577 has been purified and its oligomeric profile characterized by means of size exclusion chromatography and gel electrophoresis. DR_2577 was found to be organized into three hierarchical orders characterized by monomers, stable dimers formed by the occurrence of disulphide bonds, and hexamers resulting from a combination of dimers. The structural implications of these findings are discussed providing new elements for a more integrated model of this S-layer.